2016
DOI: 10.1016/j.diabres.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Combined arteriosclerotic assessment of ankle-brachial index and maximum intima-media thickness via CCTA is useful for predicting coronary artery stenosis in patients with type 2 diabetes

Abstract: We developed a novel formula to predict coronary artery stenosis using five predictive factors. This formula is useful for determining whether computed tomography (CT) examination is necessary, even in clinical settings without CCTA equipment. Early detection of coronary artery stenosis in patients with DM may also lead to better health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The study results indicate the potential value of including this simple test in cardiovascular risk stratification and supports current guidelines and recommendations ( 12 ). One Japanese study showed that ABI, hypertension, estimated glomerular filtration rate, max-IMT (thickest points for the intima-media thickness in the common carotid arteries, carotid bulb, and internal carotid arteries) and use of diabetic medication were independent predictive factors for coronary artery stenosis in patients with type 2 DM, and the authors built a novel formula to predict coronary stenosis in type 2 DM patients using these five factors ( 13 ). A study of 375 patients with acute myocardial infarction showed ABI is an important predictor of polyvascular disease and is a useful and simple measurement that appeared to be predictive in widespread atherosclerosis among these patients ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study results indicate the potential value of including this simple test in cardiovascular risk stratification and supports current guidelines and recommendations ( 12 ). One Japanese study showed that ABI, hypertension, estimated glomerular filtration rate, max-IMT (thickest points for the intima-media thickness in the common carotid arteries, carotid bulb, and internal carotid arteries) and use of diabetic medication were independent predictive factors for coronary artery stenosis in patients with type 2 DM, and the authors built a novel formula to predict coronary stenosis in type 2 DM patients using these five factors ( 13 ). A study of 375 patients with acute myocardial infarction showed ABI is an important predictor of polyvascular disease and is a useful and simple measurement that appeared to be predictive in widespread atherosclerosis among these patients ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the following covariates to describe the population and to adjust the potential association of the ABI categories with mortality and complications of diabetes27 28: age, sex, smoking habit, body mass index (BMI) calculated as weight divided by squared height, SBP, diastolic blood pressure (DBP), pulse pressure, total serum cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides, glycated hemoglobin (HbA1c), glucose, diabetes duration, comorbidities (hypertension, atrial fibrillation, heart failure, chronic obstructive pulmonary disease, and malignant neoplasms), and medications (antidiabetic therapy, diuretics, beta-blocking agents, calcium channel blockers, agents acting on the renin–angiotensin system, other lipid modifying agents, and aspirin). Continuous variables were considered up to 1 year previous to study entry, and categorical variables were present if they were recorded in the database previous to study entry.…”
Section: Methodsmentioning
confidence: 99%